Laser-assisted dentistry, safety, and cross-infection control: A narrative review - Livia Barenghi, Alberto Barenghi, Andrea Scribante, Matteo Pellegrini, Francesco Spadari (Journal of Applied Pharmaceutical Science, 2025)
The rapidly expanding use of laser-assisted care in dentistry requires exploring all aspects of safety. The acronym laser stands for “light amplification by stimulated emission of radiation”. The laser produces a very narrow beam of electromagnetic radiation (light) and has been exploited for some innovative dental care technologies. So far, regulatory framework and laser safety issues mainly concern the prevention of some tissue damages (eye, non-target oral tissue, and non-target skin), and laser hazards (chemical, fire, and electric shock), but minimal on cross-infection prevention and control. Concerning infection prevention, it is important to remember that the outlook for infectious risk is alarming, dental patients are potentially infectious, and as with any other innovative oral-dental health technology, laser-assisted dentistry cannot claim to be free of healthcare-associated infections. The narrative review focuses on cross-infection prevention of laser-assisted dental care and includes 158 references. The search was adopted using some essential keywords from documents in databases (PubMed, Scopus) from 2010 to 2023. This study focuses on 10 important areas in results and discussion: a) international guidelines and recommendations; b) pre-procedural mouthwash before LD; c) indoor air quality during laser dentistry and recommendations for indoor air quality in dentistry; d) use of personal protective equipment; e) hand hygiene; g) reconditioning of laser safety eyewear; f) standards for the reconditioning of laser accessories; g) clinical contact surface disinfection and the use of transparent barriers; h) limitations; and i) perspectives. To ensure safety and cross-infection prevention, the study highlights the need for sound research and updated international guidelines, and better information for users with detailed recommendations for dental practitioners.
Keywords: Dentistry, safety, laser, indoor air, particulate matter, safety glasses